Ascorbic acid electrocatalytic activity in different electrolyte solutions using electrodeposited Co(OH)2 - da Silva Pelissari, Marcelo Rodrigues [UNESP]; Archela, Edson; Tarley, Cesar Ricardo Teixeira; Dall’Antonia, Luiz Henrique (Springer Nature, 2019)
The present paper describes the use of electrodeposited Co(OH)2 on transparent conducting fluorine-doped tin oxide electrode (FTO) as functional material for ascorbic acid electrooxidation in different electrolyte solutions. The structure, composition, and morphology of film were investigated through Fourier transform infrared spectroscopy (FTIR), energy-dispersive X-ray spectrum (EDS), and scanning electron microscope (SEM). The electrochemical characterization in different electrolyte solutions was carried out by cyclic voltammetry (CV) and chronoamperometry. The voltammetric profile showed the presence of two possible reactions involving almost reversible redox processes during sweeping potential in KOH solution and a single redox process in KCl solution. The Co(OH)2 film presented electrocatalytic activity in ascorbic acid electrooxidation, being the sensitivity values found were 182.3 mA L mol−1 cm−2 and 119.4 mA L mol−1 cm−2 in KOH and KCl solutions, respectively. The results showed that the electrolytic solution strongly influenced the sensitivity of the FTO/Co(OH)2 film in ascorbic acid electrooxidation reaction. Kinetic studies showed that the electrode process was controlled by mass diffusion. In addition, chronoamperometric technique was carried out to verify the stability of the electrode. The obtained results reveal a good stability of electrode in the KCl solution; once in current density terms, the results are quite similar.
Keywords: Ascorbic acid; Cobalt hydroxide; Electrodeposited; Electrooxidation